Mixed adenoneuroendocrine carcinoma of proximal stomach; a rare but sinister pathology (Journal of Pathology of Nepal, 2020)
Mixed adeno-neuroendocrine carcinoma is a rare tumor of the gastrointestinal tract comprising of both epithelial and neuroendocrine components, each representing at least 30% of the tumor. Diagnosis is based on clinical evaluation, radiological findings, histopathological features in conjunction with immunostaining with specific neuroendocrine markers such as chromogranin, synaptophysin, CD56, and markers of epithelial differentiation such as cytokeratin, CDX2, and carcinoembryonic antigen. A 50-year-old female presented with a history of dysphagia, chest pain, anorexia, and significant weight loss with normal physical findings and baseline investigations. Upper Gastrointestinal endoscopy showed growth at the gastroesophageal junction involving cardia of the stomach. Histopathological examination of the resected mass showed both adenocarcinoma and neuroendocrine carcinomatous components each involving more than 30% of total mass examined. Identifying adenocarcinoma component admixed with a high-grade neuroendocrine component is significant as the prognosis and survival of patients differ from pure adenocarcinoma.